Survey on Knowledge, Use, and Diagnostic Applicability of Special Tests for Rotator Cuff Involvement in Clinical Practice - Steven W. Forbush; William D. Bandy; Gabrielle L. Back-Kremers; Mollie Renfroe; Haley F. Downey (International Journal of Sports Physical Therapy)
# Background